Fire behaviour in a semi-arid Baikiaea plurijuga savanna woodland on Kalahari sands in western Zimbabwe - Gambiza, J.; Campbell, Bruce M.; Moe, S.R.; Frost, P. (2005)
Human-induced fires are a major disturbance in Baikiaea plurijuga woodland savannas that are economically important for timber production. Most fires occur during the late dry season, when they may severely damage woody plants. Prescribed burning during the early dry season is a management strategy to reduce fuel loads and thus the incidence of intense fires during the late dry season. There is, however, little information on fire behaviour characteristics of early dry season fires.We studied the relationship between experimental fuel conditions and fire behaviour by lighting 15 fires during the early dry season in a Baikiaea woodland. Fire intensity ranged from 25 to 1341 kW m–1, while rate of spread of fire varied between 0.01 and 0.35ms–1. Fire intensity and rate of spread were positively related to flame height, leaf-scorch height and proportion of the area burnt. The relationships suggest that fire characteristics can be retrospectively determined using a variable such as scorch height. The grass fuel load, wind speed, relative humidity and to a lesser extent fuel moisture were important predictors of rate of spread, flame height, leaf-scorch height and proportion of the area burnt, with no impact due to the litter fuel load. The grass fuel load and wind speed had a positive effect on rate of spread, whereas relative humidity and fuel moisture had a negative effect. These findings indicate that managers can predict the likely damage to woody plants during an early dry season burn by assessing the grass fuel load and weather conditions at the time of burning.